2020
DOI: 10.1093/gerona/glaa248
|View full text |Cite
|
Sign up to set email alerts
|

Aging Influences the Metabolic and Inflammatory Phenotype in an Experimental Mouse Model of Acute Lung Injury

Abstract: Increased age is a risk factor for poor outcomes from respiratory failure and acute respiratory distress syndrome (ARDS). In this study, we sought to define age-related differences in lung inflammation, muscle injury, and metabolism after intratracheal lipopolysaccharide (IT-LPS) acute lung injury (ALI) in adult (6 month) and aged (18-20 month) male C57BL/6 mice. We also investigated age-related changes in muscle fatty acid oxidation (FAO) and the consequences of systemic FAO inhibition with the drug etomoxir.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Elevated age is a risk factor for the poor outcomes of ALI/ARDS. Using an LPS-triggered ALI model in adult and aged mice, Gibbs et al (2021) assessed age-related alterations in lung inflammation, muscle injury, and metabolism. They observed that etomoxir administration resulted in an increase in the mortality of aged but not adult ALI mice, thereby confirming that the CPT system is essential for survival from severe lung injury and indicating that adult mice have improved resilience to FAO inhibition.…”
Section: Implications Of Carnitine Palmitoyltransferase System In Inflammatory Diseases and Cancersmentioning
confidence: 99%
“…Elevated age is a risk factor for the poor outcomes of ALI/ARDS. Using an LPS-triggered ALI model in adult and aged mice, Gibbs et al (2021) assessed age-related alterations in lung inflammation, muscle injury, and metabolism. They observed that etomoxir administration resulted in an increase in the mortality of aged but not adult ALI mice, thereby confirming that the CPT system is essential for survival from severe lung injury and indicating that adult mice have improved resilience to FAO inhibition.…”
Section: Implications Of Carnitine Palmitoyltransferase System In Inflammatory Diseases and Cancersmentioning
confidence: 99%
“…These changes collectively impact on appropriate epithelial responses to environmental pathogens, although the precise impact of ageing on these processes is still incompletely understood. For example, acute airway inflammatory responses to microbial stimuli are somewhat attenuated with age and appear prolonged [ 28 ]. In apparent contrast, ageing dramatically impacts on innate airway epithelial responses to non-microbial injurious triggers, including airborne allergens such as house dust mite, as shown by markedly reduced acute production of epithelial alarmins and subsequent type 2 immune responses that are critical for regenerative processes in response to injury [ 29 ].…”
Section: The Ageing Lungmentioning
confidence: 99%
“…50 Increasing attention has also been turned to the influence of systemic and muscle metabolism in mediating muscle function in critical illness. [51][52][53] The area of muscle metabolism may have important implications for nutrient delivery during ARDS and how nutrition may influence skeletal muscle function in the acute and longer-term follow-up. [54][55][56] Some ICU exposures may influence the development of ICUAW in ARDS, some of which may be modifiable.…”
Section: Neuromuscularmentioning
confidence: 99%